P-90 Advance care planning and palliative care referral in adults with systemic right ventricular failure. (20th March 2022) - Copley, Alice; Gardner, Sarah; Gopaul, Karina
Abstract : Introduction: Patients with a systemic right ventricle (sRV) following transposition of the great arteries typically develop heart failure by 40 years of age, 1 earlier than in acquired heart failure. 2 Patients with sRV failure require input from ACHD, heart failure and palliative care teams, including advance care planning (ACP). 3 The aim of our project was to describe current ACP practice and palliative care referral in patients with a sRV at an ACHD centre in Leeds. Methods: 122 patients with sRV followed up from 2016–2021 were included. Data was extracted from electronic records including timing, content and location of ACP and palliative care referral. Results: 7 patients (5.7%) had ACP and all initial discussions were with ACHD clinicians. ACP occurred during inpatient admission for 2 patients, both prompted by clinicians. 5 patients had ACP in outpatient clinic: 3 were patient-initiated, 1 clinician-initiated and in 1 it was unclear who prompted discussion. 5 patients (4.1%) died during the data collection period and median age at death was 41 years. 1 patient discussed ACP and was referred to the palliative care team 13 months before their death. Conclusions: ACP in patients with sRV failure can be challenging, with a higher risk of sudden death and many dying at a younger age than in acquired heart failure. Recent ACP guidance advocates preparing ACHD patients and their families for both unexpected and predictable deaths. 2 In our cohort, ACP often occurred in parallel with disease modifying therapy in the outpatient setting and patients and clinicians equally initiated ACP. ACHD clinicians did the majority of ACP with our cohort, which seems to be generally preferred by ACHD patients. 4 Palliative care referral rates were low in our population, however their needs are complex. ACHD and palliative care clinicians could benefit from increased collaboration to better support this patient group. References: Brida M, Diller GP, Gatzoulis MA. Systemic right ventricle in adults with congenital heart disease. Circulation 2018;137 :508–518. Schwerzmann M, et al . Recommendations for advance care planning in adults with congenital heart disease: a position paper from the ESC working group of adult congenital heart disease, the association of cardiovascular nursing and allied professions (ACNAP), the european association for palliative care (EAPC), and the international society for adult congenital heart disease (ISACHD), European Heart Journal 2020;41 (43):4200–4210. Jaarsma T. et al . Advanced heart failure study group of the HFA of the ESC. Palliative care in heart failure: a position statement from the palliative care workshop of the Heart Failure Association of the European Society of Cardiology. Eur J Heart Fail 2009;11 (5):433–43. Tobler D, et al . Knowledge and preference for advance care planning by adults with congenital heart disease. Am J Cardiol 2012;109 :1797–1800.